Micro-/nanobubble oxygenation irrigation enhances soil phosphorus availability and yield by altering soil bacterial community abundance and core microbial populations - Bian, Qingyong; Dong, Zhiduo; Zhao, Yupeng; Feng, Yaozu; Fu, Yanbo; Wang, Zhiguo; Zhu, Jingquan; Ma, Liang (Frontiers in Plant Science, 2025)
This study aimed to explore the combined effects of conventional irrigation (CF) and micronano bubble oxygenation irrigation (MB) on enzyme activity, microbial communities, and soil phosphorus availability in the rhizosphere soil of maize. The results showed that compared to CF treatment, MB treatment significantly increased available phosphorus content and alkaline phosphatase activity in maize rhizosphere soil by 21.3% and 15.4%, respectively. Furthermore, MB significantly influenced bacterial diversity in the maize rhizosphere soil but did not considerably affect fungal diversity. Specifically, MB regulated the microbial community structure in the maize rhizosphere by altering the relative abundances of the bacterial phylum Firmicutes and fungal phyla Mucoromycota, Chytridiomycota, and Basidiomycota. In addition, MB reduced the complexity of the bacterial network while increasing the interaction density among bacterial species. Meanwhile, MB enhanced the complexity of the fungal network. Structural equation modeling indicated that MB primarily promoted soil alkaline phosphatase activity by regulating bacterial community diversity, thereby enhancing soil phosphorus availability. In conclusion, the application of micro-nano bubble oxygenation irrigation enhances the activity of alkaline phosphatase in the soil by modulating the microbial community within the rhizosphere, thereby facilitating increased phosphorus availability in the rhizosphere of maize.